Itqān as a Mediator of Product Competitiveness among Local Ice Cream Entrepreneurs - Widya Fitriyana; Syaparuddin Razak; Rina Novianty (ISTIKHLAF: Jurnal Ekonomi, Perbankan dan Manajemen Syariah, 2026)
This study analyzes the mediating role of Itqān in enhancing product competitiveness among local ice cream entrepreneurs in Bone Regency, Indonesia.Grounded in Behavioral Change Theory and Economic Empowerment and Access Theory, it explains how empowerment processes shape ethical work behavior.The research focuses on access to resource capital, changes in entrepreneurial attitudes and knowledge, and community empowerment.Itqān is conceptualized as a value-based work ethic emphasizing precision, perseverance, and quality orientation. A quantitative explanatory design was applied using survey data from 160 micro-scale entrepreneurs. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that community empowerment significantly improves access to resources and entrepreneurial cognition. These factors strongly encourage the internalization of Itqān. Itqān emerges as the strongest predictor of product competitiveness. The findings confirm that ethical commitment and disciplined work behavior are crucial drivers of sustainable market advantage.